2006
DOI: 10.1007/s11010-006-0996-4
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical study of the anti-diabetic action of the Egyptian plants Fenugreek and Balanites

Abstract: Fenugreek and Balanites are two plants commonly used in Egyptian folk medicine as hypoglycemic agents. In the present study, the effects of 21 days oral administration of Fenugreek seed and Balanites fruit extracts (1.5 g/kg bw) on the liver and kidney glycogen content and on some key liver enzymes of carbohydrate metabolism in STZ-diabetic rats were studied. In addition, the effects of these two plant extracts on the intestinal alpha-amylase activity in vitro and starch digestion and absorption in vivo were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
51
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 29 publications
3
51
0
6
Order By: Relevance
“…10,11) In this context, antioxidant property of Chaga attracts much attention. Although it was reported that polyphenolic fraction of Chaga extract showed antioxidant activity, the structures of the antioxidant principle were left unclear.…”
mentioning
confidence: 99%
“…10,11) In this context, antioxidant property of Chaga attracts much attention. Although it was reported that polyphenolic fraction of Chaga extract showed antioxidant activity, the structures of the antioxidant principle were left unclear.…”
mentioning
confidence: 99%
“…In addition, fenugreek has been shown to influence the insulin cell-signaling pathway (Broca et al, 2004;Vijayakumar et al, 2005), increasing glucose uptake in insulin sensitive tissues. These effects, along with the up-regulation of metabolic enzymes (Raju et al, 2001;Vats et al, 2003;Mohamad et al, 2004;Gad et al, 2006;Mohammad et al, 2006) and increased muscle and liver glycogen storage (Vats et al, 2003;Ruby et al, 2005;Gad et al, 2006), are consistent with the adaptations that occur with regular exercise training, suggesting that fenugreek supplementation may increase exercise capacity.…”
Section: Introductionmentioning
confidence: 76%
“…Chronic 4-OH-Ile supplementation in the form of fenugreek has shown promising results in alleviating symptoms of diabetes in rodents (Raju et al, 2001;Vats et al, 2003;Mohamad et al, 2004;Thakran et al, 2004;Gad et al, 2006;Mohammad et al, 2006;Narender et al, 2006) and in humans (Madar et al, 1988;Sharma et al, 1990;Sowmya & Rajyalakshmi, 1999;Abdel-Barry et al, 2000;Gupta et al, 2001). These studies have demonstrated a decrease in blood glucose (Madar et al, 1988;Sharma et al, 1990;Abdel-Barry et al, 2000;Gupta et al, 2001;Raju et al, 2001;Vats et al, 2003;Mohamad et al, 2004;Gad et al, 2006;Mohammad et al, 2006), total cholesterol (Sharma et al, 1990Sowmya & Rajyalakshmi, 1999;Narender et al, 2006), triglycerides (Sharma et al, 1990;Gupta et al, 2001;Narender et al, 2006), free fatty acids (Narender et al, 2006), and an increase in HDL cholesterol (Gupta et al, 2001) and pancreatic -cell insulin release (Sauvaire et al, 1998). In addition, fenugreek has been shown to influence the insulin cell-signaling pathway (Broca et al, 2004;Vijayakumar et al, 2005), increasing glucose uptake in insulin sensitive tissues.…”
Section: Introductionmentioning
confidence: 99%
“…This type of inhibitor can be used to treat type 2 diabetes mellitus and obesity. [3][4][5][6] Phaseolamin is a glycoprotein that was characterized in 1975, is present in white beans and kidney beans (Phaseolus vulgaris), and contains an a-amylase inhibitor termed a-AI. 7 Moreover, phaseolamin is used as a dietary supplement and is present in pharmaceutical products marketed as protein concentrates for weight management.…”
Section: Introduction Dmentioning
confidence: 99%